القواعد والضوابط الفقهية وأثارها في نوازل الزينة عند المرأة - حاقة, تبر; بوخشبة, رحاب; الأطرش, عائشة (University of Eloued-جامعة الوادي, 2019)
اىتمت الدراسة ب " القواعد والضوابط الفقهية وآثارىا في نوازل الزينة عند المرأة " انطلاقا من العديد من الإشكالات أهمها: ما مدى ظهور القواعد والضوابط الفقهية في النوازل الميتجدة للمرأة من جانب التجميل بهدف إظهار أثر القواعد الفقهية والضوابط في ىذه الميألة، حيث قيمت ىذه الدراسة إلى مدخل مفاىيمي لتعريف المصطلحات ومبحثنٌ الَول بعنوان ماىية الزينة في الفقو الإسلامي وحكمها الشرعي أما المبحث الثاني فكان عنوانو القواعد والضوابط الفقهية وآثارىا في نوازل الزينة عند المرأة. وخلص البحث إلى جملة من النتائج أهمها: أن الإسلام حرم من الزينة الَشكال الموىومة التي فيها ضرر على جيم المرأة حفاظا على دينها وخلقها وحماية لها من تغنً خلق الله والحث على الاعتدال في الزينة والاتزان في الإنفاق بعيدا عن الإسراف والتبذير. English Abstract The study concerned the "rules and jurisprudential rules and their effects in the ornamental insults in women" based on many of the most important problems: the extent of the emergence of rules and jurisprudential rules in the emerging humiliations of women by cosmetics in order to show the effect of the rules of jurisprudence and controls in this matter, Conceptual definition of terminology and the first two articles entitled What is adornment in Islamic jurisprudence and jurisprudence? The second section was entitled Rules and disciplines of jurisprudence and its effects in the ornamental locks in women. The research concluded with a number of results, the most important of which are: That Islam is deprived of adornment of the forms that are harmful to the body of women to preserve their religion and create and protect them from changing the creation of God and urge moderation in the adornment and balance in spending away from wasteful andwasteful
مذكرة ليسانس
Keywords: القواعد /الضوابط الفقهية /نوازل الزينة /المرأة; Règles/contrôles jurisprudentiels/incidents de parure/femmes